Effects of increasing zinc oxide on starter pig growth performance - J W Smith II; B T Richert; K Q Owen; W B Nessmith Jr; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1995)
Four hundred and twenty pigs (initially 9.8 lb and 13 d of age) were used to evaluate the effects of increasing zinc oxide in starter diets. Results that suggest 3,000 ppm and 2,000 ppm zinc, from zinc oxide, improve growth performance in phase I and II diets, respectively.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Starter; Zinc; Oxide; Performance